Occurrence and temporal variation of antibiotics and antibiotic resistance genes in hospital inpatient department wastewater: Impacts of daily schedule of inpatients and wastewater treatment process. (April 2022) - Cai, Min; Wang, Zhenglu; Gu, Haotian; Dong, Hui; Zhang, Xu; Cui, Naxin; Zhou, Li; Chen, Guifa; Zou, Guoyan
Abstract: The temporal variation of antibiotics and ARGs as well as the impact of daily schedule of inpatients on their regular occurrence in hospital wastewater (HWW) were previously obscure. In this study, the wastewater of the inpatient department pre- and posttreatment (hydraulic retention time = 8 h) was collected intraday and intraweek. The absolute concentrations of antibiotics/metabolites and ARGs in HWW were analyzed to investigate the temporal variations of their occurrence levels. Fluoroquinolones were the predominant drugs used in the inpatient department (681.30–881.66 ng/mL in the effluent) and the main contaminant in the outlet of the disinfection pond (538.29–671.47 ng/mL). Diurnal variations peaked at 19:00 for most antibiotics and ARGs, while the maximum of them occurred on weekends. Aminoglycoside resistance genes (AMRGs, 21.6–23000 copies/mL) and β -lactam resistance genes (BLGRs, 1.24–8500 copies/mL) were the dominant ARGs before and after treatment processing, respectively ( p < 0.05). The significant removal rates (>50%) of most antibiotics and ARGs, as well as the integrase gene intI 1 and 16S rRNA gene, were found to be subjected solely to the chloride disinfection process, suggesting the necessity of the self-contained wastewater treatment process. Meanwhile, the statistically significant correlation among antibiotics, ARGs, intI 1, and 16S rRNA ( p < 0.05) demonstrated that the risk of selective pressure, horizontal transfer and vertical propagation of ARGs in the effluent of the hospital was warranted. Principal component analysis (PCA) showed that the daily schedule of inpatients and wastewater treatment processes could markedly induce fluctuations in antibiotic and ARG levels in HWW, indicating that they should be considered an impact factor for environmental monitoring. This study demonstrated for the first time the temporal variations in the abundance and dissemination of antibiotics and ARGs in a semiclosed zone and provided new insight into the development of assessments of the associated ecological risk and human health. Graphical abstract: Image 1 Highlights: Flouroquinolones were the predominant antibiotics in untreated wastewater in inpatient department. Aminoglycoside resistant genes were the dominant genes in effluent. The peak of the contaminants showed at 19:00 intraday and weekends intraweek. Disinfection process effectively removed antibiotics and antibiotic resistance genes. Daily schedule of inpatients impacted the occurrence of antibiotic resistant genes.